Documenting domestication : new genetic and archaeological paradigms - Zeder, Melinda A. (University of California Press, 2006)
Agriculture is the lever with which humans transformed the earth over the last 10,000 years and created new forms of plant and animal species that have forever altered the face of the planet. In the last decade, significant technological and methodological advances in both molecular biology and archaeology have revolutionized the study of plant and animal domestication and are reshaping our understanding of the transition from foraging to farming, one of the major turning points in human history. This groundbreaking volume for the first time brings together leading archaeologists and biologists working on the domestication of both plants and animals to consider a wide variety of archaeological and genetic approaches to tracing the origin and dispersal of domesticates. It provides a comprehensive overview of the state of the art in this quickly changing field as well as reviews of recent findings on specific crop and livestock species in the Americas, Eurasia, and Africa. Offering a unique global perspective, it explores common challenges and potential avenues for future progress in documenting domestication.